Advanced issue resolution in safety pharmacology - Kallman, Mary Jeanne; Pugsley, Michael K. (Academic Press, an imprint of Elsevier, 2019)
Chapter 7. Self-Injurious Behavior in Clinical and Preclinical Populations: Description, Etiology, and Management; Introduction; Self-Injurious Behavior Overview; Self-Injurious Behavior in Nonhuman Experimental Subjects; Summary; Chapter 8. Approaches for Early Identification of Abuse Potential Liability; Introduction; Which Compounds Present an Issue for Preclinical Drug Abuse Liability Assessment?; An Integrated Approach for Assessment of Drug Abuse Liability; Examples of Abuse Liability Issue Resolution; Summary and Conclusions